Prevalência e Associação de Sintomas de Ansiedade, Depressão e Estresse em Discentes de Graduação da Universidade Federal do Maranhão com o Nível de Atividade Física - PEREIRA, Gabriel Moreira (2024)
Introduction: Anxiety, depression, and chronic stress stand out as the most prevalent mental disorders worldwide. During and post the COVID-19 pandemic, there has been a significant increase in global prevalence, affecting individuals of all ages and populations. Among university students, estimates are even higher according to recent studies. Physical activity presents itself as a non-pharmacological treatment for the symptoms of these disorders, and it is necessary to investigate possible associations of external factors with symptoms of anxiety, depression, and stress to adopt coping actions for these disorders in universities. Aim: The main objective of this study is to assess the prevalence of symptoms of anxiety, depression, and stress in undergraduate students at the Federal University of Maranhão and to associate the symptoms with the level of physical activity. Materials and Methods: The research was approved by the Ethics Committee on Research at UFMA, and 355 students, aged 18 to 35 years, of both sexes, responded to the DASS-21, IPAQ-SF, and ABEP. The data were qualitatively analyzed and described in absolute and percentage values. Association analyses were performed using Fisher's Exact Test, using GraphPad Prism 8. Results: A prevalence of anxiety symptoms was found in 46.20% of students, depression symptoms were observed in 49.61%, and stress symptoms were observed in 26.76% of participating students. 57.74% of the students presented COVID-19 symptoms, and 72.39% of the sample had satisfactory levels of physical activity. No associations were found between prevalences and the level of physical activity. Conclusion: A high prevalence of anxiety, depression, and stress was found among students, and these prevalences were not associated with levels of physical activity or the COVID-19 symptoms.